PENGARUH REKRUTMEN, PELATIHAN, DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI PADA CV. SUMBER BARU - Putra, Faizal Rizky Handayani; Putra, Febrianur Ibnu Fitroh Sukono; Iwan Koerniawan (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study is to determine whether there is an influence between recruitment, training and career development on employee performance at CV. New Source. This study uses a quantitative approach with a questionnaire in obtaining data from respondents, totaling 39 employees, and the entire population is used as a sample. Statistical analysis method using SPSS V.24 software. Tests in this study used validity, reliability, normality test, heteroscedasticity test, multicollinearity test, T test, F test, and the coefficient of determination. Based on the results of the research that has been done, it can be concluded that recruitment, training and career development simultaneously have a significant positive effect on employee performance. Partially, the recruitment variable has a significant positive effect on employee performance. The training variable has a positive and significant effect on employee performance. Career development variable has a significant positive effect on employee performance.